Few methods for solving classification and parameter grouping problem - Гамаюн, Игорь Петрович; Безменова, Ольга Николаевна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The paper considers the features of some of the existing methods of classification of objects and grouping options. Considered non-hierarchical and hierarchical methods performed to compare.